Historical Roots and Syntactic Nature of Languages - Ağarı, Murat (Journal of History Culture and Art Research, 2021)
All languages have a common, ontological nature, and this nature cannot be changed. Although there are some differences in the fictions of languages, the general course of this ontological nature is the same in all languages. Although we are talking about an ontological nature that is the same in all languages, the differences that exist between languages affect and determine the attitudes of societies that use this language. In another respect, history is a totality of social attitudes. Therefore, the language used by society can affect the attitude of that society. In other words, societies have an attitude in such a way that the language they use is foreseen. So much so that, beyond the fictional difference, even the presence or absence of a word in any language can be decisive of a social attitude. Of course, the presence or absence of a word is a small detail in the whole; but when the peculiar fictions of languages are evaluated as a whole, the effects of social attitudes on history, which is the totality, will be seen more clearly. In this study, first of all, the concept of “language family” will be focused on by giving the “definition of language”. Then, the nature of Turkish will be discussed through the language family fiction and its reflections on history will be discussed. Turkish, English, Arabic and will be sampled throughout the study.